A Tale of Three Countries: The Impact of Covid-19 on Apparel Exports from Bangladesh, China, and Vietnam to the United States - Islam, Sadequl (Archives of Business Research, 2022)
This paper examines the effects of Covid-19 on apparel exports from Bangladesh, China and Vietnam to the United States. The paper uses monthly data on knitted and non-knitted apparel goods at disaggregate levels from January 2020 to April 2021.The findings show that Covid-19 adversely affected exports of apparel goods from these countries to the US especially during the March 2020-May 2020 period. It is evident that the performance of Vietnam in apparel exports has been better compared to China and Bangladesh.